Role of biotechnology and transgenics in bananas (Musa spp.) in Africa - Shotkoski, F.A.; Tripathi, L.; Kiggundu, A.; Arinaitwe, G.; Tushemereirwe, Wilberforce K. (International Society for Horticultural Science, 2010)
In the more developed countries, genetically engineered crops contributegreatly to agricultural productivity and sustainability. Over the last few years, thelargest growth in the adoption of genetically engineered crops has been in developingcountries and this trend is expected to continue. The multinational life sciencescompanies have been leading the way, but they are focusing primarily on a fewcrop/trait combinations that have high commercial value and occupy largeinternational markets. Because of the costs and complexity of the issues related tocrop biotechnology, many crops and traits of importance to subsistence and resourcepoor farmers around the world have been overlooked. The AgriculturalBiotechnology Support Project (ABSPII), a Cornell University-led and USAIDfunded consortium of public and private sector institutions, provides support forscientists, regulators, extension workers, farmers and the general public indeveloping countries to make informed decisions about agricultural biotechnology.When possible, ABSPII creates public-private partnerships to help leverage publicfunds to help absorb development costs and provide broader distribution channels.Since 2005, ABSPII has been working with the National Agricultural ResearchOrganization in Uganda to establish safe and cost effective programs for thedevelopment and commercialization of East African highland bananas (Musa spp.),genetically engineered for black sigatoka and nematode resistance. This paper givesa brief description of the work that has been done to date and discuss the ABSPIIbased strategy that has been adopted to develop and deliver genetically engineeredcrops for developing countries.